Radiosonde‐Derived Temperature Inversions and Their Association With Fog Over 37 Melt Seasons in East Greenland. Issue 17 (3rd September 2018) - Gilson, Gaëlle F.; Jiskoot, Hester; Cassano, John J.; Nielsen, Tyrell R.
Abstract: We present temperature inversion characteristics during fog and nonfog conditions at three east Greenland coastal weather stations during Arctic melt seasons 1980–2016. For this purpose, we developed a novel automated method to extract fog‐top height (FTH) from Integrated Global Radiosonde Archive data, which is applicable to any fog thermodynamic profile and includes an improved interpolation of saturation between sounding levels. From the analysis of >22, 000 melt‐season soundings we conclude that inversions occur 85–95% of the time, are predominantly elevated, and have median depths >200 m. Fog at high‐Arctic locations often penetrates the inversion layer, especially in the late melt season, and is commonly several hundred meters thick. At low‐Arctic locations fog is thinner and generally restricted to the mixed layer. Inversions during fog are deeper and stronger compared to nonfog conditions. This effect is more pronounced at higher latitudes, which we attribute to distinct local boundary layer conditions and large‐scale processes. The Integrated Global Radiosonde Archive‐extracted FTHs have a cumulative error of 56 m and are in reasonable agreement with retrievals from Cloud‐Aerosol Lidar and Infrared Pathfinder Satellite Observation satellite cloud top data. The novel FTH extraction method can be applied to any polar sounding with >5 significant levels below 700 hPa and can be extended to boundary layer clouds other than fog, which represent the majority of cloud occurrence in the Arctic melt season. This study advances the understanding of interactions between low clouds and temperature inversions and improves retrieval of cloud geometrical thickness from radiosondes: both have important implications for the Arctic surface energy budget. Plain Language Summary: Understanding how air temperature changes with height is important for weather forecasting and climate prediction. Usually air becomes colder as it rises in the atmosphere, except during temperature inversions when air near the ground is coldest. Inversions are common in polar regions, where they often occur together with fog during summer. Fog is a cloud at the Earth surface and influences temperature inversions by modifying air temperature and the amount of solar energy reaching the Earth surface. Up until now we did not have an adequate method to calculate fog thickness from weather balloon measurements (radiosondes). In this study we present an innovative method to calculate fog‐top height using >22, 000 summer radiosonde measurements taken at three stations in east Greenland from 1980 to 2016. Temperature inversions are almost always present, more than 200 m in vertical depth, and their base often starts more than 100 m above the ground. Fog is commonly 75‐ to 250‐m deep and often penetrates the inversion layer. Temperature inversions during fog are deeper and have a larger temperature difference between top and base compared to nonfog conditions. We tested our method using independent techniques and recommend that it can be applied to most radiosonde measurements worldwide. Key Points: A novel dew point depression method is presented for the calculation of fog‐top height from radiosonde profiles Temperature inversions are 100‐m deeper and twice as strong under fog conditions compared to nonfog conditions Arctic sea fog over coastal east Greenland is often several hundred meters thick